2019
DOI: 10.1002/pts.2439
|View full text |Cite
|
Sign up to set email alerts
|

Improved heat shrinkage and mechanical performances of polyethylene trilayer blown film prepared via novel multilayer coextrusion method

Abstract: In this work, polyethylene (PE) trilayer blown film was prepared using a self‐made rotating coextrusion blown film die (RCBD) with the aim to manufacture trilayer film with excellent comprehensive heat shrinkage and mechanical performances. Polymer resins in this unique blown film die are subjected to a complicated flow field combining both shear circulation and pressure flow. As a result, the melt shows a helix movement in our novel die. The effect of additional parameter (mandrel rotation speed) on the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…On the other hand, TD orientation is achieved through the inflation of air, which causes the increase in the bubble diameter and the stretching of the polymer mainly in this direction. This orientation is related to the BUR [ 5 ]. It is worthy to note that polymer orientation in MD and TD occurs below the frost line height, between the glass transition and the melting temperature of the polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, TD orientation is achieved through the inflation of air, which causes the increase in the bubble diameter and the stretching of the polymer mainly in this direction. This orientation is related to the BUR [ 5 ]. It is worthy to note that polymer orientation in MD and TD occurs below the frost line height, between the glass transition and the melting temperature of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Menges et al [ 7 ] found that for low-density polyethylene (LDPE) blown film, changing the die geometry can allow us to obtain balanced shrinkage in MD and TD and the increase in the frost line height can led to an increase the shrinkage in the TD, with a very low influence in the MD. Luo et al [ 5 ] prepared a polyethylene (PE) three-layer film using a film blowing plant equipped with a rotating die, and they found that the mandrel rotation speed significantly improved the shrinkage of the film in the TD rather than BUR. Moreover, Torres et al [ 8 ] developed a tool to predict the extrusion blowing processing, mechanical and shrink properties of PE blends.…”
Section: Introductionmentioning
confidence: 99%
“…Heat shrinkage and mechanical properties have been reported in some articles. [12][13][14][15] Some kinds of polymer films have been adopted for the fabrication of shrinkable films. Polystyrene (PS) possesses a high heat-shrinkable property.…”
Section: Introductionmentioning
confidence: 99%
“…Tubular structures with multilayer annular structures (MAS) have been widely used in many applications, for example, as multilayered bubbles in blown films, , as a multilayered coating on wires and cables, as multilayered parisons for blown molding, and as multilayered tubes and pipes. , MAS is currently produced by a multimanifold die, in which the individual layer forms in separate manifolds and then joins together before the exit of the die . So, designing and manufacturing a multimanifold MAS die becomes rapidly complex with each added layer, putting a limit on the layering capabilities, and thus the typical MAS only includes 2–12 layers .…”
Section: Introductionmentioning
confidence: 99%
“…This technique breaks the limiting capacity of layer number in the conventional multilayer producing system and thus may bring some positive effects on the multilayer pipes and tubes field. The main contributions of this effort can be summarized as follows:(1) The custom-made annular die is designed with its flow channel gradually wrapped from the rectangular inlet into the annular outlet, and its optimum geometry is obtained by numericallysimulating the flow behavior of the multiplayer streams. (2) Because of the transverse flow driven by the shearing force from the nonradial surface of the designed die, the layer distorts toward the radial direction and thus forms the layer destruction at the welding region.…”
mentioning
confidence: 99%